(untitled) (Journal of Hama University, 2019)
The study is conducted on 18 cows as over age milk production of Holstein crossed breed.The studied animals aged between (5-8) years ,all studied animals are in stage of dried.According to Job Ramela records,the diary cows are of medium level production, the mean of milk yields is (15-17)kg. The studied animals are classified into 3 groups:1-the first group: control group: The number of cows is (6)cows, all cows are exposed to milk fever in last their births according to information of station,they left without any procedure that do not given the powder /Gel 2- the second group :the first experimen group that given the powder.The total number of group was 6 cows .They exposed to in last births to milk feve according to informtion of station .They give Calcium chlorid as powder form in order prevention of milk fever.3- the third group : the second tril group ,that given the Gel: The total number of population in this group was 6 cows , that is exposed to in last births to milk fever according to informtion of station,which given Calcium chlorid as Gel form in order to prevention of milk fever. It is obtained of blood sera for detection of biochemical parameters (Calicium, Phosphour, Magenisium). It is measured of significant variams of biochemical parameters of the mentioned values within each group and other. It was reported that adminstration of calicium chlorid orally as Gel form.It is giving success results in prevention of the disease in comparison with grained form , becouse of slow absorpation and long time effect.